Carbon Nanotube Reinforced CdSe Inverse Opal with Crack‐Free Structure and High Conductivity for Photovoltaic Applications. Issue 2 (12th December 2014) - Zheng, Xue‐Li; Qin, Wen‐Jing; Ling, Tao; Pan, Cao‐Feng; Du, Xi‐Wen
<x xml:space="preserve">Abstract</x> A crack‐free CdSe inverse opal structure is obtained by using carbon nanotubes as reinforcements, and the inverse opal structure exhibits high conductivity and excellent photoelectrical properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>